إستراتيجية مقترحة لتطوير النظام الإيكولوجي لريادة الأعمال المرتكز على الجامعة: دراسة حالة - سعد، السيدة محمود إبراهيم (جامعة عين شمس - كلية التربية, 2020)
تزايد الاهتمام في الآونة الأخيرة بدراسة مجال ريادة الأعمال في الجامعات؛ لما يحدثه من أثر في تحسين الاقتصاد ونمو سوق العمل، وزيادة الفرص الوظيفية. وقد سعى البحث الحالي إلى تحديد الإطار المفاهيمي للنظام الإيكولوجي لريادة الأعمال المرتكز على الجامعة، وتحليل أبرز النماذج العالمية الرائدة في هذا المجال؛ لتقديم نموذج مقترح والذي كان مواجها للدراسة الميدانية. استخدم البحث أبرز تطبيقات المنهج الوصفي، وهو ما يعرف بمدخل الجمع المنهجي، وهو مدخل استقرائي قائم على دراسة الحالة، وتم استخدام الاستبانة لتحديد درجة توافر عناصر النظام الإيكولوجي المرتكز على الجامعة من وجهة نظر القيادات الأكاديمية: (عميد كلية-وكيل كلية-رئيس قسم أكاديمي)؛ بكليات جامعة الإسكندرية، وقد بلغ عددهم (95) قائد/ة في العام (2018/2019). وكان من أهم النتائج التي توصل إليها البحث: أن إجمالي توافر عناصر النظام الإيكولوجي لريادة الأعمال في جامعة الإسكندرية جاء بدرجة "متوسطة"، وقد جاءت العناصر البشرية في المرتبة الأولى بدرجة توافر "عالية"، بينما جاءت العناصر المالية/المادية في المرتبة الأخيرة بدرجة توافر "متوسطة"، كما وجدت فروق دالة إحصائيا عند مستوى الدلالة (0.01) في درجة تقدير أفراد عينة البحث حول إجمالي توافر عناصر النظام الإيكولوجي لريادة الأعمال؛ تعزى للمنصب القيادي وتخصص الكلية، بينما لم تكن هناك فروق دالة إحصائيا تعزى لسنوات الخبرة. وأخيرا تم وضع استراتيجية مقترحة لتطوير النظام الإيكولوجي لريادة الأعمال المرتكز على الجامعة، في جامعة الإسكندرية.
Recent interest in studying the field of entrepreneurship in universities has increased; because of its impact on improving the economy and the growth of the labor market and increase job opportunities. The present research has sought to identify conceptual framework for the university- based entrepreneurship ecosystem (U-BEE), and to analyze the leading global studies and models in this field to provide a proposed model prepared by the researcher, which was directed to the field study. The research used the most prominent applications of the descriptive approach, which is known as the "Systematic Combining Approach", which is an inductive approach based on case study. The questionnaire was used as a research tool to determine the degree of availability of the elements of the university-based entrepreneurship ecosystem from the point of view of academic leaders (Dean, Vice Dean, Head of Academic Department) at the faculties of Alexandria University , where the number - research sample - (95) leaders in the academic year (2018/2019). The most important results of the research is that the total availability of the elements of the entrepreneurial ecosystem at Alexandria University came with a "medium" degree, and the human elements came in the first place with a "high" availability, while the financial / physical elements came in the last place with a "medium" availability Also, there were statistically significant differences at the level of significance (0.01) in the degree of estimation of the members of the research sample about the total availability of the elements of the entrepreneurship ecosystem due to the leadership position and the college’s specialization, while there are no statistically significant differences attributed to the years of experience. Finally a proposed strategy for the development of the university-based entrepreneurship ecosystem was presented, at the Alexandria University.
Keywords: الاستراتيجيات التدريسية -- النظم الإيكولوجية -- ريادة الأعمال -- الإدارة التربوية -- الاسكندرية